Intercultural competence as a succes factor of virtual multicultural teams : a case study on the team effectiveness of global HR teams - Zimmermann, Kristin (2010)
This study’s main objective is to construct a model of intercultural competence for global virtual teams in order to investigate the influence of intercultural competence on multicultural virtual team effectiveness.